Bancatakaful concept and implementation - Mat Jubri @ Shamsuddin, Muhamad Fadzli (IIUM Press, International Islamic University Malaysia, 2017)
BancatÉkaful is a new distribution channel which has been adopted from the bancasurrance concept. It has now become a major distribution channel and major contributor to the development of the takÉful industry. The study examines the concept of bancatakÉful and how it is implemented particularly in Malaysia. PruBSN Takaful is chosen as a sample of the research and the implementation of bancatakÉful in the family takÉful products of PruBSN Takaful has been analyzed. The study discusses the prospect and development of the takÉful industry, particularly the bancatakÉful channel in Malaysia.